High-temperature-resistant composite covalent organic framework humidifying film and preparation method thereof

By constructing a high-temperature resistant covalent organic frame crystal layer in the humidification film, combining the non-solvent phase separation process and the steam-assisted crystallization process, the problem of mutual restriction of selectivity and permeability of the humidification film under high temperature conditions is solved, and efficient and stable water management performance is achieved, which is suitable for high-temperature and high-humidity environments of fuel cells.

CN119524648AActive Publication Date: 2025-02-28HAINAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411713382.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The existing humidification films have mutually restricted water vapor/air selectivity and water vapor permeability under high temperature conditions, and have poor application stability and are difficult to meet the high-temperature and high-humidity working conditions of fuel cells.

Method used

A composite covalent organic frame humidification film is adopted, and the high-temperature covalent organic frame crystal layer is constructed through the combination of covalent organic frame with polysulfone materials, combined with a non-solvent phase separation process and a steam-assisted crystallization process, thereby enhancing the high-temperature tolerance and application stability of the film.

Benefits of technology

It realizes high water vapor/air selectivity and water vapor permeability of the humidification film under high temperature conditions, improves the application stability and durability of the film, and is suitable for high-temperature and high-humidity environments of fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524648A_ABST
    Figure CN119524648A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant composite covalent organic framework humidifying film and a preparation method thereof. The film comprises the following components: a covalent organic framework crystallization layer and a film matrix formed by a polysulfone material. According to the method, a non-solvent phase separation process and a steam-assisted crystallization process are coupled, and the method is an important attempt for humidifying the high-temperature tolerance of the film by using a crystalline porous skin layer. According to the prepared composite covalent organic framework humidifying film, the covalent organic framework is formed by in-situ steam composition on the surface of the film, so that the covalent organic framework can be stably anchored on the surface of a film substrate, and the film is endowed with high temperature resistance and high application stability; the crystallization layer can realize accurate screening of water vapor and air by utilizing the pore size and hydrophilic design of the crystallization layer, and endows the composite covalent organic framework with high water vapor / air selectivity; the finger-shaped pore structure of the membrane matrix has developed porosity and can enhance the permeability of water vapor in the membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of novel separation membrane materials, relates to the development of membrane materials used in the field of proton exchange membrane water management for fuel cells, and specifically relates to a high-temperature resistant composite covalent organic framework humidification membrane and a preparation method thereof. Background Art

[0002] The upstream hydrogen energy industry of the hydrogen energy and fuel cell industry chain meets the needs of my country's energy transformation, and the downstream new energy vehicle market is growing rapidly. Both the upstream and downstream of the industry chain are blue ocean markets with good prospects. Most hydrogen fuel cells are proton exchange membrane fuel cells, and the hydration state of the proton exchange membrane plays a decisive role in the performance and life of the fuel cell. Therefore, the reaction gas entering the fuel cell stack must be humidified, and the membrane humidifier has become the mainstream solution adopted by current hydrogen energy vehicles.

[0003] At present, most membrane humidifiers in the world use polysulfone membranes (polyethersulfone, polysulfone and polyphenylsulfone, etc.) as polymer matrices. The hydrophilicity, temperature resistance and mechanical properties of the humidifying membrane materials are adjusted by optimizing the process path and strengthening the materials in situ, so as to achieve the directional design and wide coverage of humidifier products. Despite this, the research and development of high-temperature resistant humidifying membrane materials is still a bottleneck. This is mainly due to the fact that under high-temperature conditions, the movement of the polymer chain segments in the humidifying membrane intensifies, causing the membrane structure to collapse and increasing the mass transfer resistance. High temperature will weaken the intermolecular interactions in the humidifying membrane, weaken its mechanical properties, and cause the membrane to break and leak easily when impacted by airflow. High temperature working conditions will also cause the decomposition or performance attenuation of polymers, porogens and enhancers in the humidifying membrane, thereby inhibiting the humidification efficiency of the membrane. As can be seen from the above, high-temperature resistant humidifying membranes face extremely arduous scientific and technological challenges, and the development of high-performance high-temperature resistant humidifying membranes has become a technological frontier and a major demand in the field. Summary of the invention

[0004] In view of the above, the present invention provides a high-temperature resistant composite covalent organic framework humidification membrane and a preparation method thereof, combines a covalent organic framework with a traditional polymer, couples a non-solvent phase separation process with a steam-assisted crystallization process to design a composite humidification membrane structure, and constructs a high-temperature resistant covalent organic framework crystal layer on the surface of the polymer matrix to solve the problems existing in the prior art such as the mutual restriction of water vapor / air selectivity and water vapor permeability of the humidification membrane under high temperature conditions and poor application stability.

[0005] To achieve the above object, the technical solution of the present invention is implemented as follows:

[0006] A method for preparing a composite covalent organic framework humidifying membrane comprises the following steps:

[0007] (1) dispersing a polysulfone material, polyvinyl pyrrolidone, and polyethylene glycol in an organic solvent to obtain a casting solution;

[0008] (2) preparing an organic solvent / water mixture with a volume fraction of 40% to 90% as a coagulation bath;

[0009] (3) applying the casting solution of step (1) onto a glass plate, allowing it to stand for a while, transferring it to a coagulation bath for immersion, taking it out, and drying it at 25 to 120° C. for 1 to 72 hours to obtain a membrane matrix;

[0010] (4) preparing an organic solution A of a covalent organic framework aldehyde monomer with a mass concentration of 0.1% to 0.5%, immersing the membrane matrix in the organic solution A, maintaining it at 25 to 60° C. for 10 to 30 seconds, and then taking it out and standing it at room temperature for 4 to 8 hours;

[0011] (5) preparing an organic solution B containing a covalent organic framework amino monomer with a mass concentration of 0.15% to 0.75%, transferring the organic solution B to a heating kettle, and fixing the membrane matrix on the top of the heating kettle with the membrane matrix surface facing downward; resetting the nitrogen gas in the heating kettle, setting the heating kettle temperature to 80 to 150° C., and obtaining a high-temperature resistant composite covalent organic framework humidification membrane.

[0012] Further, in step (1), the polysulfone material includes one or more combinations of polysulfone, polyethersulfone, polyphenylsulfone, sulfonated polysulfone, sulfonated polyethersulfone, and sulfonated polyphenylsulfone;

[0013] In step (1), the organic solvent is any one of dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dichloromethane, carbon tetrachloride, and N-methylpyrrolidone.

[0014] In step (2), the organic solvent is any one of dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dichloromethane, carbon tetrachloride, and N-methylpyrrolidone.

[0015] Furthermore, in step (1), the mass concentration of the polysulfone material in the casting solution is 14% to 22%, the mass concentration of polyvinyl pyrrolidone is 0.2% to 5%, and the mass concentration of polyethylene glycol is 0.2% to 5%.

[0016] Furthermore, in step (4), the covalent organic framework aldehyde monomer is one of trimesaldehyde and trialdehyde phloroglucinol; and in step (5), the covalent organic framework amino monomer is one of diaminobenzenesulfonic acid and diaminobenzoic acid.

[0017] Furthermore, in step (4), the organic solvent used in the organic solution A is any one of dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dichloromethane, carbon tetrachloride, and N-methylpyrrolidone;

[0018] In step (5), the organic solvent used in the organic solution B is any one of methanol, ethanol, toluene and dichloromethane.

[0019] Furthermore, in step (3), the standing time is 5-15 seconds and the soaking time is 5-15 minutes.

[0020] Furthermore, in step (5), the rotation speed of the membrane top workbench is set to 1 to 20 r / s, and the evaporation time is set to 1 to 48 h.

[0021] A high temperature resistant composite covalent organic framework humidifying membrane is prepared by any preparation method described in the present invention.

[0022] Furthermore, the high temperature resistant composite covalent organic framework humidification membrane comprises the following components: a covalent organic framework crystal layer and a matrix composed of a polysulfone material; wherein the covalent organic framework crystal layer is uniformly distributed on the outer surface of the matrix, forming a high temperature resistant crystalline cortex with a thickness of 100 to 200 nm and a roughness of 60 to 80 nm; the cross-section of the polysulfone matrix is ​​a finger-like pore structure, forming a composite covalent organic framework humidification membrane with a thickness of 100 to 300 μm.

[0023] Furthermore, in the composite covalent organic framework humidifying membrane, the material of the covalent organic framework crystal layer is any one of trimesaldehyde-p-phenylenediamine, trimesaldehyde-2,5-diaminobenzenesulfonic acid, trimesaldehyde-2,5-diaminobenzoic acid, trimesaldehyde-2,5-diaminobenzenephosphonic acid, trialdehyde phloroglucinol-p-phenylenediamine, trialdehyde phloroglucinol-2,5-diaminobenzenesulfonic acid, trialdehyde phloroglucinol-2,5-diaminobenzoic acid, and trialdehyde phloroglucinol-2,5-diaminobenzenephosphonic acid.

[0024] Furthermore, the high temperature resistant composite covalent organic framework humidification membrane of the present invention is used in the water management process of the proton exchange membrane of the fuel cell.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] In the high temperature resistant composite covalent organic framework humidification membrane prepared by the present invention, the membrane comprises the following components: a covalent organic framework crystal layer and a membrane matrix composed of a polysulfone material; wherein the covalent organic framework crystal layer is evenly distributed on the outer surface of the membrane matrix, forming a crystalline skin layer with a thickness of 100 to 200 nm and a roughness of 5 to 20 nm; the cross section of the polysulfone matrix is ​​a finger-like pore structure, forming a composite covalent organic framework humidification membrane. The present invention couples the non-solvent phase separation process with the steam-assisted crystallization process, and is an important attempt to improve the high temperature tolerance of the humidification membrane with a crystalline porous skin layer. The prepared composite covalent organic framework humidification membrane, because the covalent organic framework is formed by in-situ steam composition on the membrane surface, it can be firmly anchored on the membrane matrix surface, giving the membrane high temperature resistance and high application stability; the crystal layer can use its pore size and hydrophilic design to achieve accurate screening of water vapor and air, giving the composite covalent organic framework high water vapor / air selectivity; the finger-like pore structure of the membrane matrix has a developed porosity, which can enhance the permeability of water vapor in the membrane. Therefore, the high temperature resistant composite covalent organic framework humidification membrane disclosed by the present invention is stable and efficient in the water management process of the proton exchange membrane of the fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic flow diagram of an implementation method of the method for preparing the high temperature resistant composite covalent organic framework humidifying membrane of the present invention;

[0028] Figure 2 is a scanning electron microscope image of the high temperature resistant composite covalent organic framework humidifying membrane of Example 1 of the present invention, wherein Figure 2 a is the cross-sectional morphology of the membrane, Figure 2 b is the outer surface morphology of the membrane. Figure 2 c is the surface roughness map of the film.

[0029] Figure 3 is a scanning electron microscope image of the high temperature resistant composite covalent organic framework humidifying membrane of Example 2 of the present invention, wherein Figure 3 a is the cross-sectional morphology of the membrane, Figure 3 b is the outer surface morphology of the membrane. Figure 3 c is the surface roughness map of the film.

[0030] Figure 4 is a scanning electron microscope image of the composite covalent organic framework membrane of Comparative Example 1 of the present invention, wherein Figure 4 a is the cross-sectional morphology of the membrane, Figure 4 b is the outer surface morphology of the membrane. Figure 4 c is the surface roughness map of the film.

[0031] Figure 5 is a scanning electron microscope image of the composite covalent organic framework membrane of Comparative Example 2 of the present invention, wherein Figure 5 a is the cross-sectional morphology of the membrane, Figure 5 b is the outer surface morphology of the membrane. Figure 5 c is the surface roughness map of the film. DETAILED DESCRIPTION

[0032] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0033] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0034] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0035] Table 1 Chinese meaning

[0036]

[0037]

[0038] The structural formula of the trialdehyde phloroglucinol used in this embodiment is as follows:

[0039]

[0040] Membrane humidifier is one of the key components of hydrogen heavy trucks, used to maintain high temperature and high humidity conditions of battery stacks. However, the humidification membrane, as its "chip", faces challenges such as low humidification efficiency, poor application stability and insufficient impact resistance, which to some extent restricts the development of this field.

[0041] In order to solve the above problems, the applicant provides a high temperature resistant composite covalent organic framework humidification membrane and its preparation method, which couples the non-solvent phase separation process and the steam-assisted crystallization process, and is an important attempt to improve the high temperature tolerance of the humidification membrane with a crystalline porous skin. The prepared composite covalent organic framework humidification membrane, because the covalent organic framework is formed by the in-situ steam composition on the membrane surface, it can be firmly anchored on the surface of the membrane matrix, giving the membrane high temperature resistance and high application stability; the crystal layer can use its pore size and hydrophilic design to achieve precise screening of water vapor and air, giving the composite covalent organic framework high water vapor / air selectivity; the finger-like pore structure of the membrane matrix has a developed porosity, which enhances the permeability of water vapor in the membrane.

[0042] The high temperature resistant composite covalent organic framework humidification membrane of the present invention comprises the following components: a covalent organic framework crystal layer and a membrane matrix composed of polysulfone materials.

[0043] Specifically, the covalent organic framework crystal layer of the present invention is uniformly distributed on the outer surface of the membrane, forming a high-temperature resistant crystalline cortex with a thickness of 100 to 200 nm and a roughness of 60 to 80 nm; the cross-section of the polysulfone matrix of the present invention is a double-layer finger-like pore structure, forming a high-temperature resistant composite covalent organic framework humidification membrane with a thickness of 100 to 300 μm and a tensile strength of 8 to 10 MPa.

[0044] In one embodiment, the material of the covalent organic framework crystalline layer of the present invention is any one of trimesaldehyde-p-phenylenediamine (TFB-PPA), trimesaldehyde-2,5-diaminobenzenesulfonic acid (TFB-PPA-SO3H), trimesaldehyde-2,5-diaminobenzoic acid (TFB-PPA-CO2H), trimesaldehyde-2,5-diaminophenylphosphonic acid (TFB-PPA-PO4H2), trialdehyde phloroglucinol-p-phenylenediamine (TP-PPA), trialdehyde phloroglucinol-2,5-diaminobenzenesulfonic acid (TP-PPA-SO3H), trialdehyde phloroglucinol-2,5-diaminobenzoic acid (TP-PPA-CO2H), and trialdehyde phloroglucinol-2,5-diaminophenylphosphonic acid (TP-PPA-PO4H2).

[0045] In one embodiment, the polysulfone material of the present invention includes one or more combinations of polysulfone, polyethersulfone, polyphenylsulfone, sulfonated polysulfone, sulfonated polyethersulfone, and sulfonated polyphenylsulfone.

[0046] The applicant also provides a method for preparing the above-mentioned high temperature resistant composite covalent organic framework humidification membrane, such as Figure 1 As shown, Figure 1 It is a schematic flow chart of an embodiment of a method for preparing a high temperature resistant composite covalent organic framework humidifying membrane according to the present invention.

[0047] S100, respectively dispersing a polysulfone material, polyvinyl pyrrolidone, and polyethylene glycol in an organic solvent selected from one or more combinations of dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dichloromethane, carbon tetrachloride, and N-methylpyrrolidone, to obtain a casting solution having a polysulfone material mass concentration of 14% to 22%, a polyvinyl pyrrolidone mass concentration of 0.2% to 5%, and a polyethylene glycol mass concentration of 0.2% to 5%.

[0048] The role of the organic solvent is to fully dissolve the polysulfone material.

[0049] S200, preparing an organic solvent / water mixture with a volume fraction of 40% to 90% as a coagulation bath, wherein the organic solvent is any one of dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dichloromethane, carbon tetrachloride, and N-methylpyrrolidone.

[0050] S300, then preparing a flat membrane by a non-solvent phase separation method, drying at 25-120° C. for 1-72 hours to obtain a membrane matrix on the outer surface.

[0051] S400, prepare an organic solution A of a covalent organic framework aldehyde monomer with a mass concentration of 0.1% to 0.5%, wherein the solvent used is any one of dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dichloromethane, carbon tetrachloride, and N-methylpyrrolidone; immerse the membrane matrix in the organic solution A, keep it at 25 to 60° C. for 10 to 30 seconds, take it out and let it stand at room temperature for 4 to 8 hours.

[0052] S500, prepare an organic solution B of a covalent organic framework amino monomer with a mass concentration of 0.15% to 0.75%, and the solvent used is any one of methanol, ethanol, toluene, and dichloromethane. Transfer the organic solution B to a heating kettle, and fix the membrane matrix on the top of the heating kettle with the membrane matrix surface facing downward. Reset the nitrogen in the heating kettle, set the heating kettle temperature to 80 to 150°C, set the rotation speed of the membrane top workbench to 1 to 20 r / s, and set the evaporation time to 1 to 48 hours. With the diffusion, contact and reaction of organic vapor B on the surface of the membrane matrix, a high-temperature resistant composite covalent organic framework humidification membrane can be obtained on the workbench.

[0053] Example 1

[0054] A high temperature resistant composite covalent organic framework humidifying membrane is prepared by the following steps:

[0055] (1) Weigh 45 g of polyethersulfone, 1.5 g of polyvinyl pyrrolidone, 1.5 g of polyethylene glycol and 252 g of N-methylpyrrolidone, add them into a mixing kettle in sequence, stir mechanically for 12 h at 50° C., and stir at a speed of 100 rpm. After standing for 12 h to degas, a casting solution is obtained.

[0056] (2) A 40% by volume N-methylpyrrolidone / water mixed solution was prepared and transferred to a 20° C. coagulation bath furnace as a coagulation bath.

[0057] (3) The casting solution was scraped onto a glass plate, allowed to stand for 10 seconds, and then transferred to a coagulation bath and immersed for 10 minutes. After being taken out, the solution was dried at 50°C for 24 hours to obtain a membrane matrix.

[0058] (4) Prepare a dimethylformamide solution A with a mass concentration of 0.1% trimesaldehyde, immerse the membrane matrix in the organic solution A, keep it at 25° C. for 10 seconds, take it out and let it stand at room temperature for 8 hours.

[0059] (5) Prepare an ethanol solution B of 2,5-diaminobenzenesulfonic acid with a mass concentration of 0.15%, transfer the solution B to a heating kettle, and fix the membrane matrix on the top of the heating kettle with the membrane matrix surface facing downward. Reset the nitrogen in the heating kettle, set the heating kettle temperature to 80°C, set the rotation speed of the membrane top workbench to 10r / s, and set the evaporation time to 1h. As the organic vapor B diffuses, contacts and reacts on the surface of the membrane matrix, a high-temperature resistant composite covalent organic framework humidification membrane is obtained on the workbench.

[0060] Example 2

[0061] A high temperature resistant composite covalent organic framework humidifying membrane is prepared by the following steps:

[0062] (1) Weigh 50 g of polyphenylsulfone, 5 g of polyvinyl pyrrolidone, 10 g of polyethylene glycol and 235 g of dimethylformamide, add them into a mixing kettle in sequence, stir mechanically for 12 h at 50° C., and stir at a speed of 100 rpm. After standing and degassing for 12 h, a casting solution is obtained.

[0063] (2) A 40% by volume N-methylpyrrolidone / water mixed solution was prepared and transferred to a 20° C. coagulation bath furnace as a coagulation bath.

[0064] (3) The casting solution was scraped onto a glass plate, allowed to stand for 10 seconds, and then transferred to a coagulation bath and immersed for 10 minutes. After being taken out, the solution was dried at 50°C for 24 hours to obtain a membrane matrix.

[0065] (4) Prepare a dimethylformamide solution A of trialdehyde phloroglucinol with a mass concentration of 0.1%, immerse the membrane matrix in the organic solution A, keep it at 25° C. for 15 seconds, take it out and let it stand at room temperature for 24 hours.

[0066] (5) Prepare a methanol solution B of diaminobenzoic acid with a mass concentration of 0.15%, transfer the solution B to a heating kettle, and fix the membrane matrix on the top of the heating kettle with the membrane matrix surface facing downward. Reset the nitrogen in the heating kettle, set the heating kettle temperature to 90°C, set the rotation speed of the membrane top workbench to 10r / s, and set the evaporation time to 1.5h. As the organic vapor B diffuses, contacts and reacts on the surface of the membrane matrix, a high-temperature resistant composite covalent organic framework humidification membrane can be obtained on the workbench.

[0067] Comparative Example 1

[0068] A composite covalent organic framework membrane is prepared by the following steps:

[0069] The steps of raw material preparation of the membrane matrix, coagulation bath molding, immersion of the membrane matrix in solution A, and steam-assisted assembly of solution B are kept the same as in Example 1, and only the treatment conditions after the membrane matrix is ​​taken out of the coagulation bath are changed, that is, the membrane matrix is ​​immersed in the coagulation bath for 10 minutes, taken out and dried in the shade at 20°C for 0.5 hours, and then steam-assisted assembly is performed to obtain a composite covalent organic framework membrane.

[0070] Comparative Example 2

[0071] A composite covalent organic framework membrane is prepared by the following steps:

[0072] The steps of raw material preparation of the membrane matrix, coagulation bath molding and drying treatment, immersion of the membrane matrix in solution A, and preparation of solution B were kept the same as in Example 1, and only the temperature of the steam-assisted assembly process was changed, that is, the heating kettle temperature was set to 200°C, the rotation speed of the membrane top workbench was set to 10 r / s, and the evaporation time was set to 1 h, and then a composite covalent organic framework membrane was obtained.

[0073] Comparative Example 3

[0074] A polysulfone membrane is prepared by the following steps:

[0075] Weigh 45g polyethersulfone, 1.5g polyvinylpyrrolidone, 1.5g polyethylene glycol and 252g N-methylpyrrolidone, add them to the mixing kettle in sequence, stir mechanically for 12h at 50℃, stir at 100rpm, and stand for degassing for 12h to obtain the casting solution. Prepare a 40% N-methylpyrrolidone / water mixture, and transfer it to a 20℃ coagulation bath furnace as a coagulation bath. Scrape the casting solution onto a glass plate, let it stand for 10s, transfer it to the coagulation bath and soak it for 10min, take it out and dry it at 50℃ for 24h to obtain a polysulfone membrane. That is, this comparative example only prepares the membrane matrix.

[0076] Comparative Example 4

[0077] A composite covalent organic framework membrane is prepared by the following steps:

[0078] (1) Weigh 50 g of polyphenylsulfone, 5 g of polyvinyl pyrrolidone, 10 g of polyethylene glycol and 235 g of dimethylformamide, add them into a mixing kettle in sequence, stir mechanically for 12 h at 50° C., and stir at a speed of 100 rpm. After standing and degassing for 12 h, a casting solution is obtained.

[0079] (2) A 40% by volume N-methylpyrrolidone / water mixed solution was prepared and transferred to a 20° C. coagulation bath furnace as a coagulation bath.

[0080] (3) The casting solution was scraped onto a glass plate, allowed to stand for 10 seconds, and then transferred to a coagulation bath and immersed for 10 minutes. After being taken out, the solution was dried at 50°C for 24 hours to obtain a membrane matrix.

[0081] (4) Prepare a 1% mass concentration of trialdehyde phloroglucinol in dimethylformamide solution A, immerse the membrane matrix in the organic solution A, keep it at 25° C. for 15 seconds, take it out and let it stand at room temperature for 24 hours.

[0082] (5) Prepare a methanol solution B of diaminobenzoic acid with a mass concentration of 1.5%, transfer the solution B to a heating kettle, and fix the membrane matrix on the top of the heating kettle with the membrane matrix surface facing downward. Reset the nitrogen in the heating kettle, set the heating kettle temperature to 90°C, set the rotation speed of the membrane top workbench to 10r / s, and set the evaporation time to 1.5h. As the organic vapor B diffuses, contacts and reacts on the surface of the membrane matrix, a high-temperature resistant composite covalent organic framework humidification membrane can be obtained on the workbench.

[0083] The main difference from Example 2 is the concentration of solutions A and B in steps (4)-(5).

[0084] Effect example 1:

[0085] The high temperature resistant composite covalent organic framework humidifying membrane prepared in Example 1 was characterized and analyzed by scanning electron microscopy and atomic force microscopy, and the results were as follows: Figure 2 . Figure 2 The following are scanning electron microscope images and atomic force microscope images of the high temperature resistant composite covalent organic framework humidification membrane of Example 1 of the present invention. Figure 2 As shown, the high temperature resistant composite covalent organic framework humidification membrane prepared in Example 1 is a double-layer structure, the skin thickness is 165nm, the membrane surface is smooth, the roughness is 8.2nm, and the matrix is ​​a finger-like pore structure.

[0086] Effect example 2:

[0087] The high temperature resistant composite covalent organic framework humidifying membrane prepared in Example 2 was characterized and analyzed by scanning electron microscopy and atomic force microscopy, and the results were as follows: Figure 3 . Figure 3 The following are scanning electron microscope images and atomic force microscope images of the high temperature resistant composite covalent organic framework humidification membrane of Example 2 of the present invention. Figure 3 As shown, the high temperature resistant composite covalent organic framework humidification membrane prepared in Example 2 is a double-layer structure, the skin thickness is 180nm, the membrane surface is smooth, the roughness is 10.8nm, and the matrix is ​​a finger-like pore structure.

[0088] Effect example 3:

[0089] The high temperature resistant composite covalent organic framework humidifying membrane prepared in Comparative Example 1 was characterized and analyzed by scanning electron microscopy and atomic force microscopy, and the results were as follows: Figure 4 . Figure 4 The following are scanning electron microscope images and atomic force microscope images of the composite covalent organic framework membrane prepared in Comparative Example 1 of the present invention. Figure 4 As shown, the composite covalent organic framework membrane prepared in Comparative Example 1 has a double-layer structure, the skin thickness is about 50 nm, there are protruding particles on the membrane surface, the roughness is 27.4 nm, and the matrix is ​​a finger-like pore structure.

[0090] Effect Example 4:

[0091] The high temperature resistant composite covalent organic framework humidifying membrane prepared in Comparative Example 2 was characterized and analyzed by scanning electron microscopy and atomic force microscopy, and the results were as follows: Figure 5 . Figure 5 The following are scanning electron microscope images and atomic force microscope images of the composite covalent organic framework membrane prepared in Comparative Example 2 of the present invention. Figure 5 As shown, the composite covalent organic framework membrane prepared in Comparative Example 2 has a double-layer structure, the skin thickness is about 100 nm, the membrane surface presents a discontinuous cluster particle morphology, the roughness is 50.3 nm, and the matrix has a finger-like pore structure.

[0092] From the results of effect examples 1-4, it can be seen that the membrane matrix treatment process before entering the steam-assisted assembly and the evaporation process of the steam-assisted assembly process are particularly critical to the structure of the composite covalent organic framework membrane. If the surface of the membrane matrix is ​​not fully dried, such as in comparative example 1, the liquid remaining on its surface and in the internal pores will affect the continuous contact between the aldehyde monomer of solution A and the amino monomer of solution B, resulting in a thin and uneven cortex of the produced covalent organic framework; if the evaporation rate of solution B is too fast, such as in comparative example 2, it will cause the aldehyde monomer on the surface of the matrix to contact the amino monomer too quickly in a short time, making it difficult to match the time of crystallization reaction and generation, resulting in a loose cortex of the covalent organic framework and a high degree of roughness.

[0093] Effect Example 5:

[0094] The membranes prepared in Example 1, Example 2, Comparative Example 3 and Comparative Example 4 were respectively encapsulated into membrane modules with epoxy resin AB glue, 1 bar of water vapor or air was introduced into the membrane modules, the gas flow was monitored with a soap film flowmeter, the water vapor permeability and water vapor / air selectivity of each fiber membrane were calculated, and the water vapor permeability of the fiber membrane after water vapor was continuously introduced into the membrane module for 200 hours at 120°C was examined, and the data in the following table were obtained.

[0095] Table 1 Comparison of membrane performance of the embodiments and comparative examples

[0096]

[0097] As can be seen from the data in the table above, the water vapor / air selectivity of the high temperature resistant composite covalent organic framework humidification membranes prepared in Examples 1 and 2 is significantly higher than that of the membranes in Comparative Examples 3 and 4; among them, the water vapor / air selectivity of the high temperature resistant composite covalent organic framework humidification membrane for humidification prepared in Example 2 is as high as 1853, which is about 3 to 8 times that of the comparative membrane, and the water vapor permeability is 0.15 g min -1 cm -2 MPa -1 The permeability attenuation at 120°C for 200 hours is less than 7%. The water vapor permeability of the composite membrane prepared in Example 1 is 0.17 g min -1 cm -2 MPa -1 , and the permeability attenuation after durability is less than 12%. The composite covalent organic framework humidification membrane prepared in the above Examples 1 and 2 shows excellent high temperature humidification performance. This is mainly due to the special structure of the high temperature resistant composite covalent organic framework humidification membrane prepared in Examples 1 and 2. It uses the covalent organic framework crystal layer as the outer skin layer, and can fully utilize its regular and rigid channel structure to accurately size-screen water vapor and air molecules, giving the membrane high water vapor / air selectivity, making it between 1620 and 1850; the developed microporous structure of the polysulfone porous layer in the membrane strengthens the transmembrane transmission of water vapor molecules, giving the membrane high water vapor permeability, making it reach 0.15 to 0.17 g min -1 cm -2 MPa -1 However, since Comparative Example 3 does not contain a covalent organic framework crystal layer, and the reaction concentration of the covalent organic framework material in Comparative Example 4 exceeds the critical value, it is difficult to form a continuous and stable crystalline layer on the membrane surface, thereby inhibiting the performance of the composite membrane.

[0098] Although the present invention has been described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can make many modifications without departing from the purpose of the present invention, all of which are within the protection of the present invention.

Claims

1. A method for preparing a composite covalent organic framework humidification membrane, characterized in that: The following steps are involved: (1) dispersing a polysulfone material, polyvinyl pyrrolidone, and polyethylene glycol in an organic solvent to obtain a casting solution; (2) preparing an organic solvent / water mixture with a volume fraction of 40% to 90% as a coagulation bath; (3) applying the casting solution of step (1) onto a glass plate, allowing it to stand for a while, transferring it to a coagulation bath for immersion, taking it out, and drying it at 25 to 120° C. for 1 to 72 hours to obtain a membrane matrix; (4) preparing an organic solution A of a covalent organic framework aldehyde monomer with a mass concentration of 0.1% to 0.5%, immersing the membrane matrix in the organic solution A, maintaining it at 25 to 60° C. for 10 to 30 seconds, and then taking it out and standing it at room temperature for 4 to 8 hours; (5) preparing an organic solution B containing a covalent organic framework amino monomer with a mass concentration of 0.15% to 0.75%, transferring the organic solution B to a heating kettle, and fixing the membrane matrix on the top of the heating kettle with the membrane matrix surface facing downward; resetting the nitrogen gas in the heating kettle, setting the heating kettle temperature to 80 to 150° C., and obtaining a high-temperature resistant composite covalent organic framework humidification membrane.

2. The preparation method according to claim 1, characterized in that: Step (1), the polysulfone material includes one or more combinations of polysulfone, polyethersulfone, polyphenylsulfone, sulfonated polysulfone, sulfonated polyethersulfone, and sulfonated polyphenylsulfone; Step (1), the organic solvent is any one of dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dichloromethane, carbon tetrachloride, and N-methylpyrrolidone; In step (2), the organic solvent is any one of dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dichloromethane, carbon tetrachloride, and N-methylpyrrolidone.

3. The preparation method according to claim 1, characterized in that: In step (1), the mass concentration of the polysulfone material in the casting solution is 14% to 22%, the mass concentration of polyvinyl pyrrolidone is 0.2% to 5%, and the mass concentration of polyethylene glycol is 0.2% to 5%.

4. The preparation method according to claim 1, characterized in that: Step (4), the covalent organic framework aldehyde monomer is one of trimesaldehyde and trialdehyde phloroglucinol; In step (5), the covalent organic framework amino monomer is one of diaminobenzenesulfonic acid and diaminobenzoic acid.

5. The preparation method according to claim 1, characterized in that: Step (4), the organic solvent used in the organic solution A is any one of dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dichloromethane, carbon tetrachloride, and N-methylpyrrolidone; In step (5), the organic solvent used in the organic solution B is any one of methanol, ethanol, toluene and dichloromethane.

6. The preparation method according to claim 1, characterized in that: Step (3), the standing time is 5-15s, and the soaking time is 5-15min; Step (5), setting the rotation speed of the membrane top workbench to 1-20 r / s, and setting the evaporation time to 1-48 h.

7. A high temperature resistant composite covalent organic framework humidifying membrane, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.

8. The high temperature resistant composite covalent organic framework humidifying membrane according to claim 1, characterized in that: It includes the following components: A matrix composed of a covalent organic framework crystal layer and a polysulfone material; wherein the covalent organic framework crystal layer is evenly distributed on the outer surface of the matrix, forming a high-temperature resistant crystalline cortex with a thickness of 100 to 200 nm and a roughness of 60 to 80 nm; the cross-section of the polysulfone matrix is ​​a finger-like pore structure, forming a composite covalent organic framework humidification membrane with a thickness of 100 to 300 μm.

9. The composite covalent organic framework humidifying membrane according to claim 8, characterized in that: The material of the covalent organic framework crystal layer is any one of trimesaldehyde-p-phenylenediamine, trimesaldehyde-2,5-diaminobenzenesulfonic acid, trimesaldehyde-2,5-diaminobenzoic acid, trimesaldehyde-2,5-diaminobenzenephosphonic acid, trialdehyde phloroglucinol-p-phenylenediamine, trialdehyde phloroglucinol-2,5-diaminobenzenesulfonic acid, trialdehyde phloroglucinol-2,5-diaminobenzoic acid, and trialdehyde phloroglucinol-2,5-diaminobenzenephosphonic acid.

10. Use of the high temperature resistant composite covalent organic framework humidification membrane described in any one of claims 7 to 9 or the high temperature resistant composite covalent organic framework humidification membrane obtained by the preparation method described in any one of claims 1 to 6 in the water management process of proton exchange membrane in fuel cells.

Citation Information

Patent Citations

  • Covalent organic framework hollow fiber membrane as well as preparation method and application thereof

    CN116926718A

  • Porous diaphragm for all-vanadium redox flow battery based on size screening and preparation method of porous diaphragm

    CN117638129A

  • Ultrahigh-flux covalent organic framework composite nanofiltration membrane and preparation method thereof

    CN117959962A

  • Microwave-assisted method for preparing covalent organic framework nanofiltration membrane and nanofiltration membrane

    CN118987971A

  • Method for producing a metal organic framework film, metal organic framework film and use of a metal organic framework film

    WO2020157051A1